Robustifying Forecasts from Equilibrium-Correction Models. - Hendry, D (Nuffield College (University of Oxford), 2004)
In a non-stationary world subject to structural breaks, where model and mechanism differ, equilibrium-correction models are a risky device from which to forecast. Equilibrium shifts entail systematic forecast failure, and indeed forecasts will tend to move in the opposite direction to the data. A new explanation for the empirical success of second differencing is proposed. We consider model transformations based on additional differencing to reduce forecast-error biases, as usual at some cost in increased forecast-error variances. The analysis is illustrated by an empirical application to narrow money holdings in the UK.